The 1838 Mormon War in Missouri - LeSueur, Stephen C. (University of Missouri Press, 1990)
While much has been written on the Mormon War in past decades, Stephen C. LeSueur takes a fresh and much-needed new look. Writing in clear, straightforward prose, LeSueur has produced a thorough and thoughtful study that makes several important contribution ...